Optimizing Digital Marketing Strategies For Indonesian Retail Companies Through SWOT Analysis And Strategic Development - Surya Budiman; Udin Ahidin (Jurnal Manajemen Industri dan Logistik, 2025)
The purpose of this study is to find the best digital marketing strategy and its development strategy for retail companies in Indonesia. This study uses a qualitative approach of SWOT analysis, and data collection through interviews and direct observation, in five retail companies in Indonesia, namely Indomart, Alfamart, Alfamidi, Carefour and Lottemart. The results of the study show that each company has advantages in terms of wide market reach, marketing cost efficiency, and ease of interaction with customers through digital platforms. However, there are challenges that need to be overcome, such as limited human resources in digital marketing, tight competition, and cybersecurity threats. As a development strategy, this study recommends several main steps, including: (1) Improving digital HR competency through technology-based marketing training, (2) Utilizing AI and Big Data technology to personalize customer experiences, (3) Diversifying digital marketing platforms, including using live shopping and influencer marketing strategies, (4) Strengthening customer data security to increase user trust, and (5) Expanding omni-channel and e-commerce services to increase sales effectiveness.